Development of a methodology to study fringe dynamics using remote sensing, geographic information systems and statistical analysis : an application in Kathmandu Valley (Nepal) - Lacoul, Mona; Andrianasolo, Haja; Delsol, Jean Pierre; Morishita, Hideharn; Government of France (Bangkok : Asian Institute of Technology, 1997)
Change is inevitable and occurs in a continuum. Whether it be the transformation of an embryo to a human form or the transposition of solitude to society, it can be termed as a "change". Constant variations cover all the spheres of life; and a life has better advantages for survival if it possesses the capability of adapting to various alterations in the vicinity. Consequently, it can be asserted that "change" is universal and covers all forms of life. Urbanization can be said as the process of conversion of natural environment into artificial setting through various stages with the flow of time. In other words, urbanization is a change in the surrounding towards the formation of urban. As a result, urbanization is considered as an important phase in the development of a society and ultimately in that of a nation. The degree of urbanization indicates how developed a society, and a nation is. However, as every coin has two sides, multitudes of problems appear hand-in-hand with the process of urbanization. Nepal, is a developing country and definitely undergoing urbanization. As a consequence, towns and cities of Nepal are facing complex problems regarding the provision and maintenance of services in face of the rapid growth of population, caused by natural increase and migration. In order to meet such challenges, a planner needs to have fairly accurate and up to date information on rapidly expanding urban areas. A study of it's trend generally helps in understanding of emerging growth pattern and in formulating policies to guide and redirect it. Recent advances in the field of remote sensing technology and computer based Geographic Information System provide very useful tools for undertaking such analysis. The results from a study about a growth trends of the urban fringe in Kathmandu valley using multitemporal data for the period 1991 to 1994 is presented. classical definitions of fringe are highly generalized. A quantitative methodology 'is tried to develop to delineate and study the fringe. Since, population is important determinant of physical expansion of the urban areas, growth of built up land is related with population in the study.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1997
Keywords: Urban geography -- Nepal -- Kathmandu Valley; Geographic information systems; Remote sensing -- Nepal -- Kathmandu Valley